2021
DOI: 10.7554/elife.62994
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis active demethylase ROS1 cis-regulates defence genes by erasing DNA methylation at promoter-regulatory regions

Abstract: Active DNA demethylation has emerged as an important regulatory process of plant and mammalian immunity. However, very little is known about the mechanisms by which active demethylation controls transcriptional immune reprogramming and disease resistance. Here, we first show that the Arabidopsis active demethylase ROS1 promotes basal resistance towards Pseudomonas syringae by antagonizing RNA-directed DNA methylation (RdDM). Furthermore, we find that ROS1 facilitates the flagellin-triggered induction of the di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
78
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 89 publications
9
78
1
Order By: Relevance
“…Supporting this hypothesis, mutations in pathways involved in DNA methylation or demethylation of TEs affect resistance to pathogens [81,[116][117][118][119]. Moreover, upregulation of defence genes relies in many cases on active DNA demethylation of TE sequences located in their promoters [120,121]. Specifically, it was shown that ROS1 antagonizes the action of RdDM over transcription factor binding sites that are adjacent to TE sequences within the promoters of defence genes, thus exacerbating their induction in response to pathogen attacks [121].…”
Section: (B) Functional Consequences Of Environmentally Induced Te-asmentioning
confidence: 98%
See 1 more Smart Citation
“…Supporting this hypothesis, mutations in pathways involved in DNA methylation or demethylation of TEs affect resistance to pathogens [81,[116][117][118][119]. Moreover, upregulation of defence genes relies in many cases on active DNA demethylation of TE sequences located in their promoters [120,121]. Specifically, it was shown that ROS1 antagonizes the action of RdDM over transcription factor binding sites that are adjacent to TE sequences within the promoters of defence genes, thus exacerbating their induction in response to pathogen attacks [121].…”
Section: (B) Functional Consequences Of Environmentally Induced Te-asmentioning
confidence: 98%
“…Moreover, upregulation of defence genes relies in many cases on active DNA demethylation of TE sequences located in their promoters [120,121]. Specifically, it was shown that ROS1 antagonizes the action of RdDM over transcription factor binding sites that are adjacent to TE sequences within the promoters of defence genes, thus exacerbating their induction in response to pathogen attacks [121]. In addition, ROS1 expression itself is quantitatively and positively coupled to the DNA methylation level of a TE sequence located in the promoter of the gene, which as a result serves as an epigenetic rheostat or 'methylstat' [122,123].…”
Section: (B) Functional Consequences Of Environmentally Induced Te-asmentioning
confidence: 99%
“…The most straightforward mechanism is cis-regulation, whereby TE hypomethylation causes regional euchromatisation, which increases the accessibility of transcriptional machinery to nearby defence genes (Wilkinson et al, 2019). For example, DNA demethylation by ROS1 facilitates MAMP-induced expression of the disease resistance gene RMG1 by limiting RdDM at the 3' boundary of a TE-derived repeat sequence embedded in its promoter (Halter et al, 2021).…”
Section: Stage 1: the Regulatory Role Of Pathogen-induced Epigenetic Changementioning
confidence: 99%
“…It is known that DNA methylation in some promoter regions may prevent transcription initiation, since DNA methylation-sensitive transcription factors cannot bind to their targets on the promoters to start transcription (39). For example, for WRKY transcription factors to bind to defense gene promoters, they need Repressor of Silencing 1 (ROS1) to demethylate DNA (40). Since the DNA methylation related-mutants used in this study have genome-wide effects on DNA methylation, we wanted to see if we could uncover some cryptic promoters in the genomes of these mutants by ONT DRS.…”
Section: Dna Methylation May Obscure Potential Transcription Start Simentioning
confidence: 99%